Sejarah Perkembangan Pemikiran Gerakan Salafiyah - Suhilman Suhilman (Buletin Al-Turas, 2005)
Salafiyah is a reform movement focusing on the matters of akidah and Islamic puritanism. The Islamic teaching should not be treated as a doctrine (das sein) in the society but it should be actualized as stipulated by al-Qur'an and Hadis (das sollen)